Time and World according to Abu Ala' Al-Ma'arri - الضاهر, سليمان; صافي, علي; كالو, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Islamic philosophy was able to add real and important additions , ideas and new topics to the philosophical thought , and it is worth mentioning that the idea of time and the world was one of these ideas in which the genius of Muslim philosophers was manifested , among them (Abu Ala' Al-Ma'arri ) . Although he was influenced by Greek philosophy , this doesn't negate the effort of this amazing character. In this research, we dealt with the peculiarity of Abu Ala' Al-Ma'arri view of the problem of the time and world . In the introduction , the philosopher was introduced and the problematic question was posed , as for the research elements , they included opinions about the idea of time , followed by an explanation of the truth and nature of time according to Abu Al-Ala' and then mentioning its types and talking about Al-Dahr (time) and nothingness , and sempiternity and eternity , then clarifying the problem of world to him. In conclusion , we concluded that Abu Al-Ala' came out with a new vision about the idea of time and the world despite his much hesitation in his books and he claimed that time and the world are sempiternal and eternal .